2016
DOI: 10.17511/ijpr.2016.i11.12
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of newborns born to mothers with prolonged rupture of membrane

Abstract: Introduction: Prolonged rupture of membrane (PROM) is an important risk factor for early onset neonatal sepsis (EONS), which is associated with increased neonatal morbidity and mortality. This study is mainly done to know the outcome of neonates born to mothers with history of PROM. Methods: This study was conducted from January 2015 to December 2015 for a period of 12 months, in GSL medical college and hospital, Rajahmundry. Selection of cases-All the neonates born to mothers with history of prolonged rupture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 7 publications
2
3
0
Order By: Relevance
“…In this study 30.4% neonates had respiratory distress, 2.4% had pneumonia, 9.6% had culture proven sepsis, 2.4% had meningitis and 5.6% had birth asphyxia. Similar results were seen in a study by Thayi et al 18 where 16.5% neonates had respiratory distress and 11.1% had sepsis, in a study by Patil et al where 26% neonates had respiratory distress, 14% has sepsis, 4% had interventricular haemorrhage and contrary finding were seen in a study by Chaangte et al 12 where 2% had sepsis, 2% had birth asphyxia and 1% had respiratory distress and this could be attributed to only term neonates being included in their study.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this study 30.4% neonates had respiratory distress, 2.4% had pneumonia, 9.6% had culture proven sepsis, 2.4% had meningitis and 5.6% had birth asphyxia. Similar results were seen in a study by Thayi et al 18 where 16.5% neonates had respiratory distress and 11.1% had sepsis, in a study by Patil et al where 26% neonates had respiratory distress, 14% has sepsis, 4% had interventricular haemorrhage and contrary finding were seen in a study by Chaangte et al 12 where 2% had sepsis, 2% had birth asphyxia and 1% had respiratory distress and this could be attributed to only term neonates being included in their study.…”
Section: Discussionsupporting
confidence: 92%
“…In this study, 28.8% had clinical sepsis and 9.6% had culture-positive sepsis, similar results were found in a study conducted by Thayi S et al 18 where clinical sepsis was observed in 30% of cases and culturepositive sepsis was observed in 11% of neonates. In a study by Nili et al 4 clinical sepsis was observed in 20.2% of cases and culture-positive sepsis was observed in 5.5% of cases.…”
Section: Discussionsupporting
confidence: 91%
“…Several other workers have reported similar finding. [5][6][7][8] Bias for male sex, place of study, sample including other factors may be responsible for increased number of male cases in these studies. Though the exact reason for this male preponderance is not known with certainty, it is probably due to the fact that the factors regulating the synthesis of Y-globulins are situated on the X-chromosome.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of sepsis was higher in low birth weight neonates when compared to normal birth weight babies, this finding was correlated with the previous studies. 6,[11][12][13] This increase incidence is because of low birth weight babies have low IgG levels as well as impaired cellular immunity and hence are more susceptible to infection. A systematic analysis of global, national and regional causes of child mortality in 2013 identified preterm birth complications and infections to be the two major causes of neonatal deaths in India.…”
Section: Discussionmentioning
confidence: 99%
“…They also concluded that PPROM was associated with adverse neonatal outcome with most common complication being Respiratory distress syndrome followed by neonatal sepsis [17]. Many other studies also reported a significant correlation between PPROM and adverse perinatal outcome [18][19][20][21]. On contrary to this, a recent study reported that PPROM per se was not associated with adverse perinatal outcome, neither was it associated with increased risk of sepsis [5].…”
Section: Original Research Articlementioning
confidence: 97%